Auxetic boosting of confinement in mortar by 3D reentrant truss lattices for next generation steel reinforced concrete members. (April 2022) - Tzortzinis, Georgios; Gross, Andrew; Gerasimidis, Simos
Abstract: A study is presented on a new method for confining concrete/mortar materials using steel auxetic truss lattice reinforcement. The study builds on major advances in architected materials and a new concept for the confinement of structural members. Numerical results are presented on a unit cell of the new composite including a mortar matrix and a steel reentrant auxetic lattice as reinforcement, followed by a small scale experimental phase where 3D printed steel auxetic lattices are encased in mortar and tested under axial compression. Several findings emerge: the auxetic lattice applies enhanced confinement to the mortar matrix, the new composite exhibits significant strength increase compared to plain mortar specimens and the composite has a remarkably ductile behavior, with a high residual strength that endures to strains in excess of 20%. The experimental results are further validated through computational modeling. The findings of this paper demonstrate the high potential of using auxetic lattices as reinforcement in a concrete/mortar matrix with advantageous properties for structures in terms of strength and ductility which are crucial in the response of structures under extreme loading conditions such as earthquakes.